The cleaning goby mutualism: a system without punishment, partner switching or tactile stimulation - Soares, Marta C.; Côté, Isabelle M.; Cardoso, S.C.; Bshary, Redouan (My University, 2008)
In the cleanerfish–client mutualism involving the Indo-Pacific cleaner wrasse Labroides dimidiatus and its reef fish clients, mechanisms such as ‘tactile stimulation’, partner switching and punishment are used by clients to control cheating by cleaners. We sought to establish whether these behaviours are general features of cleaning mutualisms by examining their presence in interactions between Caribbean cleaning gobies (Elacatinus spp.) and their clients. The cleaning goby–client mutualism bears several similarities to the cleaner wrasse system: clients visit cleaners frequently to have their ectoparasites removed while cleaners depend heavily on these visits for food, and cheating by cleaning gobies is also prevalent. However, our data revealed striking differences between the two cleanerfish systems: clients did not seem to attempt to control cheating by cleaning gobies and cleaning gobies did not perform tactile stimulation on their clients. We suggest three hypotheses that might explain these major differences between both systems, based on differences in mutual dependence between cleaners and clients or cognitive ability of cleaners, differences in costs of being cheated and differences in foraging preferences by cleaners. Interactions between L. dimidiatus and its clients should probably not be seen as the ‘standard’ marine fish cleaning mutualism.
Keywords: cleaning goby mutualism; Elacatinus spp.; cheating; partner choice; partner switching; punishment; tactile stimulation